Filling the Silence: Reactivation, not Reconstruction - Paape, Dario L. J. F. (Frontiers in Psychology, 2016)
In a self-paced reading experiment, we investigated the processing of sluicing constructions (`sluices') whose antecedent contained a known garden-path structure in German. Results showed decreased processing times for sluices with garden-path antecedents as well as a disadvantage for antecedents with non-canonical word order downstream from the ellipsis site. A post-hoc analysis showed the garden-path advantage also to be present in the region right before the ellipsis site. While no existing account of ellipsis processing explicitly predicted the results, we argue that they are best captured by combining a local antecedent mismatch effect with memory trace reactivation through reanalysis.